Development of temporal rainfall patterns for Sabah and Sarawak - Mohd Azkarmin, Mohd Adenan (Universiti Malaysia Sarawak (UNIMAS), 2010)
In general, average annual rainfall for Sabah and Sarawak ranges from 1,500 mm to 4,000 mm which are about 20 % to 40 % more rainfall than Peninsular Malaysia. This study carried out in order to develop temporal rainfall pattern for Sabah and Sarawak as it is not applicable for designation of Sabah and Sarawak flood drainage system in accordance to Peninsular Malaysia temporal pattern. 5 minutes rainfall dataset in period of 2000-2008 collected and analyzed to determine temporal rainfall pattern through Average Variability Method (AVM) which utilized from Australian Rainfall and Runoff (AR&R) 1987 and method in Hydrological Procedure No.1-1982. 11 rainfall stations which consist of 5 stations from Sabah and 6 stations from Sarawak were selected with complete and overlapping data in terms of available variables and long period of observation. Several criteria for choosing the key stations were made in order to precisely construct and generate the patterns. The result of this study showed that the temporal rainfall patterns between East Coast of Peninsular Malaysia with Sabah& Sarawak was very much different which indicates roughly about 10% in comparison. When the total rainfall amount is relatively high, this difference will give significant impact. Thus, the development of temporal rainfall pattern for Sabah and Sarawak would be best recommended as it is more relevant and represent the region specifically.